CODE MIXING IN NOVEL RANGE OF STORIES BY GITA SAVITRI DEVI AND ITS RELATION TO NOVEL TEXT - Apriani, Devita; Wirawati, Denik (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research is motivated by the use of code-mixing in the novel Range of Stories by Gita Savitri Devi. This study aims to describe the form and function of code-mixing in the novel and to relate it to teaching materials in learning novel texts for class XII SMA. This type of research is descriptive qualitative. The research subject is the novel Range of Stories by Gita Savitri Devi and the object under study is code mixing in the novel. Data collection is done by using reading and note techniques. The main instrument determinant in this research is the researcher himself. The data analysis technique used is the referential equivalent method, while the data validity technique uses intrarater and interrater. This technique is done by intensifying observations, namely by reading the novel Range of Stories repeatedly. Meanwhile, theÂ interrater technique was carried out by checking the validity of the data through supervisors and colleagues who carried out the same research. Then, data analysis using referential equivalent method. The results of this study are as follows: (1) code-mixing forms in the form of words, word groups, clauses, baster, abbreviations, and word repetitions; (2) the function of code mixing as repetition of words, display of learning, affirmation of the accuracy of meaning, and indication of uniqueness; and (3) the link between code mixing in novels and teaching materials in learning novel texts for class XII SMA based on KD 3.9 and 4.9Â AbstrakPenelitian ini dilatarbelakangi oleh penggunaan campur kode dalam novel Rentang Kisah karya Gita Savitri Devi. Penelitian ini bertujuan untuk mendeskripsikan wujud dan fungi campur kode dalam novel tersebut serta mengaitkannya dengan bahan ajar pada pembelajaran teks novel kelas XII SMA. Jenis penelitian ini yaitu kualitatif deskriptif. Subjek penelitian berupa novel Rentang Kisah karya Gita Savitri Devi dan objek yang yang diteliti adalah campur kode dalam novel tersebut. Pengumpulan data dilakukan dengan menggunakan teknik baca catat. Penentu instrumen utama dalam penelitian ini adalah peneliti sendiri. Teknik analisis data yang digunakan adalah metode padan referensial, sedangkan teknik keabsahan data menggunakan intrarater dan interrater, Teknik ini lakukan dengan mengintensifkan pengamatan, yaitu dengan membaca novel Rentang Kisah secara berulang-ulang. Sementara itu, teknik interrater dilakukan dengan mengecek keabsahan data melalui dosen pembimbing maupun teman sejawat yang melakukan penelitian yang sama. Kemudian, analisis data menggunakan metode padan referensial. Hasil dari penelitian ini sebagai berikut:(1) wujud campur kode berupa kata, kelompok kata, klausa, baster, singkatan, dan pengulangan kata; (2) fungsi campur kode sebagai pengulangan kata, pemameran keterpelajaran, penegasan ketepatan makna, dan penunjukan kekhasan; dan (3) kaitan campur kode pada novel dengan bahan ajar pada pembelajaran teks novel kelas XII SMA berdasarkan KD 3.9 dan 4.9.Â